„Siedzieć jak na tureckim kazaniu”, czyli o trudnym języku kazań - Szewczyk, Leszek (Logopedia Silesiana, 2014)
“To seat like a lemon” or on a difficult language of sermonsListening to sermons is getting more and more difficult for a contemporary man. Thismay be due to the growing discrepancy between language used and understood by listeners and thelanguage of preachers. The language of sermons and homilies is the literary one in its normative-anddidacticform. The official teaching of the Church shows that a considerable importance is attributedto the verbal sphere of preaching. The language of preaching should be correct, esthetic and contemporary.Also, it should be adequate, which is congruent with the reality it describes. In the preachingof the Word of God the content is the most important. The form of the utterance should serve thecontent.